2005
DOI: 10.1002/psc.667
|View full text |Cite
|
Sign up to set email alerts
|

Design of peptide oxytocin antagonists with strikingly higher affinities and selectivities for the human oxytocin receptor than atosiban

Abstract: The peptide oxytocin (OT) antagonist atosiban, approved for tocolytic use in Europe (under the tradename Tractocile), represents an important new therapeutic advance for the treatment of premature labor. This paper presents some new peptide OT antagonists which offer promise as superior tocolytics. The solid phase synthesis is reported of four pairs of L and D-2-naphthylalanine (L/D-2Nal) position-2 modified analogs of the following four oxytocin (OT) antagonists: des-9-glycinamide [1-(beta-mercapto-beta,beta-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 108 publications
1
16
0
Order By: Relevance
“…It was equipotent at rat OT and V2 receptors and 10-fold selective for rat OT vs. rat V1 receptors ( Table 1). The selectivity of atosiban was very similar to that reported in the literature by various groups (6,20,36). For example, Cirillo et al (6) found that atosiban was 23-fold more potent at hV1a than hOT and only 8 and 12-fold more potent at hOT than V1b and V2, respectively.…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…It was equipotent at rat OT and V2 receptors and 10-fold selective for rat OT vs. rat V1 receptors ( Table 1). The selectivity of atosiban was very similar to that reported in the literature by various groups (6,20,36). For example, Cirillo et al (6) found that atosiban was 23-fold more potent at hV1a than hOT and only 8 and 12-fold more potent at hOT than V1b and V2, respectively.…”
Section: Resultssupporting
confidence: 69%
“…Peptide antagonists that are more potent and selective than atosiban have been identified. For example, those described by both Manning et al (20) and Stymiest et al (32) are reported to be as potent as GSK221149A. However, the most selective peptide described by Manning et al (20) is only 6.5-fold selective for human OT vs. human V1a receptors, and no selectivity data are reported by Stymiest et al (32).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In vivo bioassays show that these two antagonists show selectivity for action at the oxytocin receptor over the vasopressin V 1a receptor (36). At the same time that the jugular cannulation was performed, an osmotic minipump (model 1007D, Durect Corp., Cupertino, CA) was implanted.…”
Section: Study 3: Effect Of Oxytocin Receptor Antagonistsmentioning
confidence: 99%
“…Typical experimental data are presented in Fig. 6a and are fitted (Manning et al, 2001(Manning et al, , 2005 (Fig. 6b).…”
Section: Cooperative Binding Probes Gpcr Dimer Existence 1785mentioning
confidence: 99%